THE EFFECTIVENESS OF TECHNO-ETHNO-PHYSICS LEARNING MEDIA ON STUDENTS' CRITICAL THINKING AND CREATIVITY - Krisna Suryanti; Fibrika Rahmat Basuki; Selina Damayanti (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2026)
This study aims to develop and evaluate the effectiveness of techno-ethno-physics learning media in enhancing senior high school students’ critical thinking and creativity. The study employed the Four-D (4D) development model, limited to the define, design, and develop stages. The learning media were developed by integrating physics concepts with Jambi's local wisdom and digital technology using 3D PageFlip Professional. The effectiveness of the developed learning media was evaluated using a quasi-experimental design with a nonequivalent control group. The participants consisted of 70 eleventh-grade students from MAN 2 Jambi, who were assigned to experimental and control groups. Data were collected through expert validation sheets, teacher and student response questionnaires, and tests measuring students’ critical thinking and creativity. The collected data were analyzed using normality and homogeneity tests, independent-samples t-tests, and N-gain analysis. The results showed that the developed learning media demonstrated a very high level of validity and received highly positive evaluations from both teachers (92%) and students (86%). Moreover, students in the experimental group achieved higher mean scores in critical thinking (82.86) and creativity (84.42) than those in the control group (77.43 and 73.14, respectively). The N-gain scores for critical thinking (0.58) and creativity (0.61) were both categorized as moderate, indicating meaningful improvements in students’ higher-order thinking skills. These findings demonstrate that techno-ethno-physics learning media effectively enhance students’ critical thinking and creativity.